Adding virtual reality to the university self-access language centre: Brave new world or passing fad?. Issue 2 (October 2019) - Chateau, Anne; Ciekanski, Maud; Molle, Nicolas; Paris, Justine; Privas-Bréauté, Virginie
Abstract : Immersing students in communicative situations facilitates learning, engages emotions, and fosters socio-cognitive conflicts leading learners to develop abilities (Dewaele 2010; Bourguignon 2006; Privas-Bréauté2017 ). In this context, the UFR Lansad – languages for the specialists of other disciplines – in charge of language teaching policy for non-specialist students at the University of Lorraine (France) opened a virtual reality (VR) space in which experimentations are carried out. Researchers intend to study how VR might support second language development and contribute to enhance students' cultural awareness. To do so, VR workshops are offered, VR sessions with student teachers implemented and an international collaboration experimentation in English for Specific Purposes (ESP) is under way. Although learners' reactions and feedback are very positive, the first implementation of the new VR space leads us to understand that VR and its pedagogical uses might suffer from some flaws.